Leading with humility - Nielsen, Rob; Marrone, Jennifer A.; Ferraro, Holly S. (New York Routledge, 2014)
Based on cutting edge research, this text advances a new model for understanding effective leadership. The authors advocate the idea of leading with humility, a trait that is rarely discussed and frequently misunderstood.
Introduction -- Humility -- Application.
Includes bibliographical references (pages 117-124) and index.
Keywords: Leadership -- Psychological aspects; Humility